Microsporidia-nematode associations in methane seeps reveal basal fungal parasitism in the deep sea - Sapir, Amir; Dillman, Adler R.; Connon, Stephanie A.; Grupe, Benjamin M.; Ingels, Jeroen; Mundo-Ocampo, Manuel; Levin, Lisa A.; Baldwin, James G.; Orphan, Victoria J.; Sternberg, Paul W. (Frontiers in Microbiology, 2014)
The deep sea is Earth’s largest habitat but little is known about the nature of deep-sea parasitism. In contrast to a few characterized cases of bacterial and protistan parasites, the existence and biological significance of deep-sea parasitic fungi is yet to be understood. Here we report the discovery of a fungus-related parasitic microsporidium, Nematocenator marisprofundi n. gen. n. sp. that infects benthic nematodes at Pacific Ocean methane seeps on the Pacific Ocean floor. This infection is species-specific and has been temporally and spatially stable over two years of sampling, indicating an ecologically consistent host-parasite interaction. A high distribution of spores in the reproductive tracts of infected males and females and their absence from host nematodes’ intestines suggests a sexual transmission strategy in contrast to the fecal-oral transmission of most microsporidia. N. marisprofundi targets the host’s body wall muscles causing cell lysis, and in severe infection even muscle filament degradation. Phylogenetic analyses placed N. marisprofundi in a novel and basal clade not closely related to any described microsporidia clade, suggesting either that microsporidia-nematode parasitism occurred early in microsporidia evolution or that host specialization occurred late in an ancient deep-sea microsporidian lineage. Our findings reveal that methane seeps support complex ecosystems involving interkingdom interactions between bacteria, nematodes, and parasitic fungi and that microsporidia parasitism exists also in the deep sea biosphere.